The art of design: how building blocks can transform into an autistic teen's dream career, inspiring future generations through teaching - Abdul Karim, Izza Syahida; Wan Omar, Wan Noor Faaizah; Ahmad Zawawi, Azlyn (Universiti Teknologi MARA, Kedah, 2025)
Art is a beautiful reflection of our diverse cultures, rich histories, and the unique personal styles that make each of us shine. It is a universal language, uniquely created and appreciated by every culture and individual, celebrating the beauty of human expression in countless forms.